Judge's Ijtihad Discourse In Deciding Cases Divorce Suit Of Pregnant Wives In Indonesia - Indra Sakti; Muhammad Ichsan (Jurnal Hadratul Madaniyah, 2026)
This research focuses on how judges use ijtihad in deciding divorce cases filed by wives in pregnant conditions. By using normative juridical methods and statutory, concept, and case study approaches, this research examines positive legal provisions, expert views, and related court decisions. The research results show that pregnancy cannot be used as a basis for rejecting a divorce suit. The judges use ijtihad to interpret legal rules, assess aspects of benefit, and provide protection for women in accordance with the principles of maqāṣid al-sharī'ah and the provisions in Supreme Court Regulation Number 3 of 2017. From the analysis, two patterns of judge's decisions were found: postponing the divorce until the wife gives birth or immediately granting the divorce if the continuation of the marriage is considered to endanger the wife or fetus. Thus, the judge's ijtihad becomes an important instrument in realizing more substantial justice and ensuring protection for pregnant women in divorce cases.